1996
DOI: 10.1002/eji.1830260228
|View full text |Cite
|
Sign up to set email alerts
|

P‐selectin directs T lymphocyte‐mediated injury in delayed‐type hypersensitivity responses: studies in glomerulonephritis and cutaneous delayed‐type hypersensitivity

Abstract: The role of P-selectin in T-lymphocyte accumulation and injury was studied in delayed-type hypersensitivity (DTH) responses in the skin and glomeruli of rats. Sprague Dawley rats were sensitized to sheep globulin and challenged 5 days later in the skin by subcutaneous injection and simultaneously in glomeruli by intravenous injection of a subnephritogenic dose of sheep anti-rat glomerular basement membrane globulin. This resulted in cutaneous and glomerular T lymphocyte-dependent macrophage influx and injury c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 27 publications
1
47
1
Order By: Relevance
“…Evidence from histological studies has demonstrated a role for adhesion molecule-mediated leukocyte recruitment to glomeruli (17)(18)(19)(20)(21)37). Moreover, findings such as the inhibitory effect of P-selectin blockade on leukocyte recruitment have suggested that the conventional sequence of rolling preceding adhesion applies in glomerular vessels (20,22). However, this has never been demonstrated directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from histological studies has demonstrated a role for adhesion molecule-mediated leukocyte recruitment to glomeruli (17)(18)(19)(20)(21)37). Moreover, findings such as the inhibitory effect of P-selectin blockade on leukocyte recruitment have suggested that the conventional sequence of rolling preceding adhesion applies in glomerular vessels (20,22). However, this has never been demonstrated directly.…”
Section: Discussionmentioning
confidence: 99%
“…P-selectin inhibition has been shown to reduce glomerular leukocyte recruitment and renal injury, suggesting that P-selectin-mediated rolling interactions contribute to efficient glomerular leukocyte recruitment (20,22). In contrast, other work has shown that P-selectin-deficient (P-selectin Ϫ/Ϫ ) mice have increased levels of glomerular recruitment and renal damage, suggesting that not only is P-selectin not required, it may actually inhibit glomerular leukocyte recruitment (23,24).…”
mentioning
confidence: 99%
“…P-selectin is an adhesion molecule that is expressed on platelets and several other cell types, and the level of P-selectin has been reported to be elevated in other autoinflammatory diseases, in which it has also been recognized as a circulating disease marker (11)(12)(13). The prominence of P-selectin in experimentally induced immune nephritis has also been quite extensively studied (34)(35)(36)(37). Interestingly, a protective role for endothelial P-selectin in immune nephritis has been suggested (37).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections (6 m) were stained to demonstrate CD4 ϩ cells, CD8 ϩ cells, and macrophages using a three-layer immunoperoxidase technique, as previously described (33)(34)(35). The primary mAb were GK1.5 (anti-mouse CD4, American Type Culture Collection, Manassas, VA), 53-6.7 (anti-mouse CD8, American Type Culture Collection), and M1/70 (antimouse Mac-1, American Type Culture Collection).…”
Section: Immunohistochemistry For T Cells Macrophages Nk Cells Andmentioning
confidence: 99%